Significance of level of bifurcation of common carotid artery and variant branches of external carotid artery in cervicofacial surgeries with ontological explanation: a cadaveric study - Sonje, Preeti; Kanasker, Neelesh; Vatsalaswamy, P. (International Surgery Journal, 2019)
Background: External carotid artery is the main artery supplying the structures of neck and face. Variability in the branching pattern of external carotid artery is important surgically and radiologically from the point of view of procedures carried out in that region. Purpose of the present study was to study the branching pattern of external carotid artery. Methods: Carotid triangle of the neck and the infratemporal fossa was dissected for studying the external carotid artery. Results: Generally the common carotid artery bifurcates at the level of upper border of lamina of thyroid cartilage. Level of bifurcation of common carotid artery may vary; it may arise at a lower level or at a higher level than its normal level of origin, which was observed in this study. Amongst the branches of external carotid artery like the superior thyroid artery, the facial artery, the lingual artery usually shows variations in their origin. These include origin of superior thyroid artery from common carotid artery, common trunk for facial and lingual arteries and many other different types of variations were seen in this study. Conclusions: Variant origins of the branches of external carotid artery are of significance in surgeries of thyroid, parotid gland, tongue as well as important in diagnostic procedures of head, neck, face region.